2020
DOI: 10.1016/j.radonc.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Superior outcomes of nodal metastases compared to visceral sites in oligometastatic colorectal cancer treated with stereotactic ablative radiotherapy

Abstract: Highlights SBRT for CRC results in excellent local control rates for nodal metastases. Median PFS for NM was 19 months versus 9 months for VM. Nodal site was significant prognostic factor on multivariate analysis for PFS/OS. We hypothesise an immunoediting basis for the improved outcomes of NM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…These implied that each SABR treatment site should have its own specific fractionation schedule and extra caution should be taken in terms of post-treatment toxicities with SABR treatments of high BED 10 . In agreement with O’Cathail et al, 25 the estimated median PFS of our whole cohort was 14.6 months and the multivariate Cox regression analysis suggested that CRC patients with nodal oligometastatic disease had better PFS compared to non-nodal oligometastatic disease (median 17.8 vs 10.8 months).…”
Section: Discussionsupporting
confidence: 92%
“…These implied that each SABR treatment site should have its own specific fractionation schedule and extra caution should be taken in terms of post-treatment toxicities with SABR treatments of high BED 10 . In agreement with O’Cathail et al, 25 the estimated median PFS of our whole cohort was 14.6 months and the multivariate Cox regression analysis suggested that CRC patients with nodal oligometastatic disease had better PFS compared to non-nodal oligometastatic disease (median 17.8 vs 10.8 months).…”
Section: Discussionsupporting
confidence: 92%
“…The authors collected data from 96 patients with 108 lesions (48.1% abdominal/pelvic lymph nodes) undergoing MRgRT with a median BED α/β =10 of 100 Gy, reporting 1-year freedom from local progression (FFLP), freedom from distant progression (FFDP), and PFS and OS rates of 92.3%, 41.1%, and 39.3% e 89.6%, respectively. Although these results seem to be similar to ours, the local and global disease control outcomes differ from those reported in our study, as the authors also included lymph node metastases, which are known to have a higher response to SBRT, compared to parenchymal metastases [ 29 ].…”
Section: Discussionsupporting
confidence: 79%
“…A prospective cohort was published in this oligo metastatic setting with superior outcomes for lymph node involvement versus visceral involvement (hepatic and lung metastases mainly). In this series, local control at 1 year was 90% for lymph node irradiation versus 75% for visceral lesions [8].…”
Section: Discussionmentioning
confidence: 62%